Where the Street Was Trench and Court: Confluence and Feedback Between the Working Class and the Chilean Left, 1950–1960 - Bravo Vargas, Viviana (Revista de Historia Social y de las Mentalidades, 2025)
This article’s main hypothesis is that Chile’s democratization process and the construction of the Chilean road to socialism were forged in the streets, through the articulation of social and political struggles that linked labor conflict with party action. The organized and politicized working class was a key actor in this process, strengthening the left’s project beyond its internal differences. Based on this premise, the article analyzes three forms of popular mobilization—national strikes, marches for civil liberties, and protests against price hikes and for fair wage adjustments—understood as expressions of an expanding class-based political culture during the 1950s and 1960s. The research draws on sources from the National Administrative Archive, union and party documents, parliamentary debates, and the press of the period.